Catalyst for catalytic synthesis of lactide, preparation method and method for catalytic synthesis of lactide

By introducing SO42-modified ZnO-SnO composite metal oxide substrate and polymerization inhibitor into the catalyst, the problems of low catalytic efficiency and complex process in the depolymerization reaction of lactic acid oligomers are solved, and high efficiency is achieved. Simple lactide synthesis improves product yield and light purity.

CN116474825BActive Publication Date: 2025-02-18WANHUA CHEM GRP CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210043980.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-01-14
Publication Date
2025-02-18
Estimated Expiration
2042-01-14

AI Technical Summary

Technical Problem

The existing catalysts have low catalytic efficiency in the depolymerization reaction of lactic acid oligomers, are prone to carbonization, and require expensive organometallic catalysts. The process is complex, the equipment investment is high, and the generated lactide has low light purity and low yield.

Method used

The catalyst is prepared by sol-gel method by using a catalyst supported by the ZnO-SnO composite metal oxide substrate with a structural polymerization inhibitor of Formula I to enhance the Lewis acidity of metal ions and reduce the residual polymer of high molecular weight kettle. Generation of .

Benefits of technology

Improve the thermal stability and regeneration simplicity of the catalyst, replace the organic zinc/tin catalyst, improve the yield and optical purity of lactide, avoid the generation of high molecular weight kettle residues, simplify the process flow, and reduce production costs .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116474825B_ABST
    Figure CN116474825B_ABST
Patent Text Reader

Abstract

The invention discloses a catalyst for catalytic synthesis of lactide, a preparation method and a method for catalytic synthesis of lactide. The catalyst is prepared by a sol-gel method to obtain a ZnO-SnO substrate, and SO4 2‑ Modification is performed; at the same time, the catalyst is loaded with a polymerization inhibitor of formula I during the process of preparing the catalyst. The catalyst prepared by the present invention has strong thermal stability and is easy to regenerate, and can replace organic zinc / tin catalysts. The catalyst of the present invention is used for high-temperature depolymerization of lactic acid prepolymer to obtain lactide, and the product has high yield and high optical purity, and no high molecular weight still polymer is generated, thereby avoiding the influence of high molecular weight still polymer on recycling, and can effectively simplify the reaction process and reduce production costs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of chemical synthesis, and particularly relates to a catalyst for catalytic synthesis of lactide, a preparation method and a method for catalytic synthesis of lactide. Background Art

[0002] Polylactic acid (PLA) is an important biodegradable bio-based material. It is biocompatible and bioabsorbable. It can be degraded into carbon dioxide and water in the natural environment and the human body, so it will not pollute the environment or harm the human body. Because of its unique physical properties, polylactic acid can be widely used in agricultural coatings, packaging films, medical devices and other fields.

[0003] Lactide is an important monomer for the synthesis of polylactic acid, and is usually prepared using lactic acid as raw material. The synthesis reaction of lactide requires two steps. The first step is to esterify and condense lactic acid into chain oligomers, and the second step is to depolymerize and cyclize the oligomers of lactic acid to generate lactide.

[0004] The condensation reaction of lactic acid requires acid catalysis. Lactic acid itself is an organic acid. The process can use a catalyst to catalyze the condensation, or allow lactic acid to react by itself. The depolymerization reaction of lactic acid oligomers is essentially an acid-catalyzed reaction, and it is Lewis acid catalyzed. Usually, the catalyst is required to have strong Lewis acidity, so the catalytic effect of organic tin or zinc is much higher than that of oxides or chlorides. However, the organic metal catalysts with better catalytic effects, such as stannous octoate, stannous isooctanoate, etc., are expensive. At the same time, the organic groups are prone to carbonization at the high temperature of the depolymerization reaction, which will lead to a decrease in the catalytic efficiency of the catalyst and difficulty in regeneration.

[0005] In addition, during the depolymerization of lactic acid oligomers to generate lactide, a side reaction of oligomer polymerization occurs at the same time, the molecular weight of the depolymerization kettle residue continues to increase, the viscosity increases, and the mass transfer and heat transfer effect deteriorates, resulting in further side reactions such as isomerization, a decrease in the lactide yield, and a decrease in light purity. In order to avoid the above problems in the traditional process, the depolymerization kettle residue needs to be continuously extracted, and in order to increase the yield, the kettle residue needs to be hydrolyzed and reused in the prepolymerization process, which is complex and increases equipment investment. Therefore, if the further polymerization of oligomers can be prevented in the depolymerization reaction of lactic acid oligomers, the extraction and reuse of the kettle residue will be effectively avoided, and the lactide yield and light purity will be increased. The inventors of the present application tried to directly add an inhibitor to prevent further polymerization of oligomers. Since the polymerization reaction mainly occurs on the catalyst surface, the directly added inhibitor has a poor contact effect with the catalyst, and there is a problem of poor inhibition effect. Summary of the invention

[0006] In order to solve the problems existing in the prior art, the present invention provides a catalyst for catalytic synthesis of lactide. The catalyst has strong thermal stability and is easy to regenerate. It can replace organic zinc / tin catalysts. The catalyst is used for high-temperature depolymerization of lactic acid prepolymers to obtain lactide. The product has high yield and high optical purity, and no high molecular weight residual polymer is generated.

[0007] Another object of the present invention is to provide a method for preparing the catalyst.

[0008] Another object of the present invention is to provide a method for catalyzing the synthesis of lactide using the catalyst.

[0009] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solution:

[0010] A catalyst for catalytic synthesis of lactide, the catalyst is SO4 2- A catalyst having a polymerization inhibitor of formula I loaded on a modified ZnO-SnO composite metal oxide substrate,

[0011]

[0012] Among them, w=10~40, x=20~50, y=10~20, z=30~50.

[0013] On the other hand, the preparation method of the above catalyst comprises the following steps:

[0014] 1) Precursors of zinc and tin are prepared into a solution with a solvent, and polyethylene glycol and lactic acid are added and mixed;

[0015] 2) Add ammonia water to adjust the pH value to 1-3, and place it for aging for 6-24 hours to form a gel;

[0016] 3) separating the gel by filtration, repeatedly washing with a solvent until it becomes neutral, drying, and then calcining at a high temperature to obtain a ZnO-SnO composite metal oxide substrate;

[0017] 4) mixing the ZnO-SnO composite metal oxide substrate obtained in step 3) with a certain amount of polyethylene glycol, lactide and lactic acid, and reacting them under a first reaction condition; adding a certain amount of lactide and ethylene glycol monomethyl ether to the product, and continuing the reaction under a second reaction condition;

[0018] 5) After cooling, the product was dissolved in dichloromethane, anhydrous ethanol was added for precipitation, and the precipitate was dried in vacuum;

[0019] 6) The vacuum-dried precipitate is immersed in a sulfuric acid solution, and then filtered and separated, and the filter cake is dried under vacuum conditions to obtain a catalyst.

[0020] In a specific embodiment, the precursors of zinc and tin in step 1) are selected from any one of nitrates, acetates or chlorides of zinc and tin, and the molar ratio of zinc to tin is 0.5 to 2;

[0021] Preferably, the solvent in step 1) is water or an alcohol solvent, and the concentration of the precursor after being prepared into a solution is 2 to 5 mol / L;

[0022] Preferably, the molecular weight of the added polyethylene glycol is 200-600, the mass ratio of the polyethylene glycol to the precursor is 0.1-0.3, and the mass ratio of the added lactic acid to the precursor is 0.3-0.7.

[0023] In a specific embodiment, in step 3), the baking is carried out at 100-150° C. for 3-5 hours; preferably, the high temperature calcination temperature is 300-500° C., and the calcination time is 3-5 hours.

[0024] In a specific embodiment, the molecular weight of the polyethylene glycol added for the first time in step 4) is 2000-4000, the mass of the polyethylene glycol added is 50%-300% of the mass of the ZnO-SnO composite metal oxide substrate, the mass of the lactide added is 40%-300% of the mass of the polyethylene glycol, and the mass of the lactic acid added is 0.5%-10% of the mass of the polyethylene glycol;

[0025] Preferably, in step 4), the first reaction temperature is 100-150° C., the reaction pressure is 5-50 KPaA, and the reaction time is 0.5-3 h; more preferably, the reaction temperature is 110-140° C., the reaction pressure is 10-35 KPaA, and the reaction time is 1-2.5 h.

[0026] In a specific embodiment, the lactide added for the second time in step 4) is 40% to 150% of the mass of the polyethylene glycol added for the first time, and the mass of the polyethylene glycol monomethyl ether added is 100% to 300% of the mass of the polyethylene glycol added for the first time;

[0027] Preferably, in step 4), the second reaction temperature is 120-180° C., the reaction pressure is 1-20 KPaA, and the reaction time is 0.5-3 h; more preferably, the reaction temperature is 130-170° C., the reaction pressure is 2.5-15 KPaA, and the reaction time is 1-2.5 h.

[0028] In a specific embodiment, the amount of dichloromethane added in step 5) is 5 to 20 times the mass of the product, and the volume of anhydrous ethanol added is 5 to 20 times the volume of dichloromethane; preferably, the vacuum drying temperature is 100 to 150° C., and the drying time is 3 to 10 hours.

[0029] In a specific embodiment, the concentration of the sulfuric acid solution in step 6) is 0.5-2 mol / L, and the soaking time is 6-24 hours; preferably, the drying temperature is 80-120° C., and the drying time is 1-3 hours.

[0030] In another aspect, a method for catalytically synthesizing lactide comprises using the aforementioned catalyst or the catalyst prepared by the aforementioned preparation method in the reaction of preparing lactide by depolymerizing lactic acid oligomers.

[0031] In a preferred embodiment, a method for catalytically synthesizing lactide comprises the following steps:

[0032] 1) Polycondensation of lactic acid into oligomers: lactic acid oligomers are obtained by esterification polycondensation of lactic acid;

[0033] 2) Depolymerization of lactic acid oligomers: The obtained lactic acid oligomers are mixed with the aforementioned catalyst or the catalyst prepared by the aforementioned preparation method, and a depolymerization reaction is carried out under certain conditions to generate a lactide product, and the lactide is continuously distilled off for collection.

[0034] In a specific embodiment, the lactic acid is L-lactic acid or D-lactic acid;

[0035] Preferably, in step 1), the lactic acid is subjected to an esterification polycondensation reaction at a temperature of 100 to 185° C., a pressure of 2.5 to 10 KPaA, and a residence time of 4 to 15 hours, and the water produced during the reaction is evaporated to obtain lactic acid oligomers;

[0036] Preferably, the reaction temperature of the depolymerization reaction in step 2) is 190-250° C., the reaction pressure is 0.5-5 KPaA, the residence time is 0.1-3 h, and the catalyst concentration is 0.1%-5%.

[0037] Compared with the prior art, the present invention has the following beneficial effects:

[0038] The present invention prepares ZnO-SnO composite substrate by sol-gel method, so that it has a larger specific surface area and better catalyst substructure, and introduces SO4 2- Modification can greatly enhance the Lewis acidity of metal ions, which can make up for the original zinc / tin metal oxides' insufficient Lewis acidity, resulting in the disadvantage that the catalytic activity is not as good as that of organic zinc / tin catalysts. At the same time, the catalyst does not contain organic groups, the price of raw materials for preparation is low, the method is simple, and the cost is lower than that of organic zinc / tin catalysts. At the same time, the catalyst has good thermal stability and is not easy to decompose at high temperatures of depolymerization.

[0039] The modified catalyst of the method also carries a polymerization inhibitor, which can effectively reduce the generation of high molecular weight still residue polymers during the depolymerization of lactic acid oligomers, avoid the reuse of high molecular weight still residue polymers, effectively simplify the reaction process, and reduce production costs. Compared with directly adding a polymerization inhibitor to the system, it has the advantages of more significant polymerization inhibition effect and higher product light purity.

[0040] The method for catalytically synthesizing lactide of the present invention has a crude lactide yield of up to 100% in the depolymerization reaction process, an optical purity of more than 97%, and a depolymerization kettle residual weight average molecular weight Mw less than 1750. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 This is the hydrogen spectrum of the inhibitor on the catalyst prepared in Example 1 of the present invention.

[0042] Figure 2 This is the carbon spectrum of the inhibitor on the catalyst prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0043] In order to better understand the technical solution of the present invention, the following examples will further illustrate the method provided by the present invention, but the present invention is not limited to the listed examples, and should also include any other known changes within the scope of the claims of the present invention.

[0044] A method for preparing a catalyst for catalytic synthesis of lactide comprises the following steps:

[0045] (1) preparing a solution of zinc and tin precursors with a solvent, adding polyethylene glycol and lactic acid to the solution;

[0046] (2) adding ammonia water to adjust the pH value to 1-3, and aging for 6-24 hours to form a gel;

[0047] (3) separating the gel by filtration, repeatedly washing with a solvent, drying at 110° C. for 3 to 5 hours, and then calcining at a high temperature to obtain a ZnO-SnO composite metal oxide substrate;

[0048] (4) mixing the prepared ZnO-SnO composite metal oxide with a certain amount of polyethylene glycol, lactide and lactic acid, and reacting them at a temperature of 100-150° C. and a pressure of 5-50 KPaA for 0.5-3 h; adding a certain amount of lactide and ethylene glycol monomethyl ether to the product, and reacting them at a temperature of 120-180° C. and a pressure of 1-20 KPaA for 0.5-3 h;

[0049] (5) after cooling, dissolving the product in dichloromethane with a volume of 5 to 20 times the mass of the product, adding anhydrous ethanol with a volume of 5 to 20 times the volume of dichloromethane to precipitate, and vacuum drying the precipitate;

[0050] (6) The vacuum-dried precipitate is soaked in a sulfuric acid solution for 6 to 24 hours, and then filtered and separated. The filter cake is vacuum-dried at 100° C. for 1 to 3 hours to obtain the prepared catalyst.

[0051] Wherein, in step (1), the precursors of zinc and tin include but are not limited to nitrates, acetates and chlorides, the precursor of zinc is preferably zinc acetate, and the precursor of tin is preferably stannous chloride, and the molar ratio of the two can be 0.5 to 2, for example, 0.5, 1, 1.5, 2, preferably 0.5 to 1.

[0052] In step (1), the solvent can be water or an alcohol solvent, such as the most common ethanol, and the concentration of the precursor in the prepared precursor solution is 2-5 mol / L, such as 2 mol / L, 3 mol / L, 4 mol / L, 5 mol / L, preferably 2-3 mol / L; the polyethylene glycol added in the solution acts as a coating agent to prevent the metal oxide particles from growing, and the lactic acid acts as a stabilizer to prevent the system from being destroyed during the pH adjustment process to form a hydroxide precipitate with uneven particle size; the mass ratio of polyethylene glycol to the precursor is 0.1-0.3, such as 0.1, 0.2, 0.3, and the mass ratio of lactic acid to the precursor is 0.3-0.7, such as 0.3, 0.4, 0.5, 0.6, 0.7. The molecular weight of the added polyethylene glycol is 200-600, such as polyethylene glycol 200, polyethylene glycol 400, and polyethylene glycol 600.

[0053] In step (3), the gel needs to be dried at 110°C to form a dry gel before calcination. There is no particular limitation on the drying time, for example, 3 to 5 hours. The drying time can be appropriately extended according to the water loss of the gel within the given drying time. The high-temperature calcination temperature of the dry gel can be 300 to 500°C, preferably 400 to 500°C. The calcination time can be 3 to 5 hours, preferably 4 to 5 hours.

[0054] In step (4), polyethylene glycol, lactide and the ZnO-SnO composite metal oxide obtained in step (3) are mixed at room temperature, heated to the reaction temperature and then subjected to negative pressure reaction. During the negative pressure reaction, lactic acid is gradually added dropwise, and the reaction is continued for 1-2 hours after all the lactic acid is added. The molecular weight of the added polyethylene glycol is 2000-4000, and the added mass is 50% to 300% of the mass of the ZnO-SnO composite metal oxide substrate, for example, including but not limited to 50%, 100%, 150%, 200%, 250%, 300%, more preferably 100% to 250%; the mass of the added lactide is 40% to 300% of the mass of the polyethylene glycol, for example, including but not limited to 40%, 100%, 150%, 200%, 250%, 300%, more preferably 70% to 250%; the mass of the added lactic acid is 0.5% to 10% of the mass of the polyethylene glycol, for example, including but not limited to 0.5%, 1%, 1.5%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, more preferably 1% to 5%. The reaction temperature is 110 to 140°C, more preferably 120 to 140°C. The reaction pressure is 10-35 KPaA, more preferably 10-25 KPaA. The reaction time is preferably 1-2.5 h, and the lactic acid addition time is 0.5-1 h.

[0055] The mass of lactide added again after the initial reaction is 40% to 150% of the mass of the polyethylene glycol added initially, for example, including but not limited to 40%, 50%, 60%, 70%, 80%, 90%, 100%, 110%, 120%, 130%, 140%, 150%, preferably 50% to 120%; the mass of polyethylene glycol monomethyl ether added is 100% to 300% of the mass of the polyethylene glycol added initially, for example, including but not limited to 100%, 120%, 150%, 175%, 200%, 220%, 250%, 280%, 300%, preferably 120% to 250%; the reaction temperature is 130 to 170° C., the pressure is 2.5 to 15 KPaA, and the reaction time is 1 to 2.5 h.

[0056] In step (5), the anhydrous ethanol can be added dropwise until no white precipitate is precipitated. The reason why anhydrous ethanol can be used for phase separation precipitation is that the metal oxide substrate can be well dispersed in dichloromethane, and dichloromethane can also dissolve the generated polymerization inhibitor, so that the polymerization inhibitor can be more evenly loaded on the surface of the metal oxide substrate; however, the metal oxide substrate and the polymerization inhibitor are both insoluble in ethanol, and after adding ethanol, the metal oxide loaded with the polymerization inhibitor will precipitate.

[0057] Specifically, in step 5), the amount of dichloromethane added is 5 to 20 times the mass of the product, and the volume of anhydrous ethanol added is 5 to 20 times the volume of dichloromethane; the vacuum drying temperature is 100 to 150° C., and the drying time is 3 to 10 hours.

[0058] In step (6), the concentration of the sulfuric acid solution can be 0.5 to 2 mol / L. When the concentration of the sulfuric acid solution is too high, a portion of sulfate will be generated on the substrate surface and solid acid cannot be obtained. Therefore, the concentration should not exceed 2 mol / L. The preferred value of the concentration is 0.5 to 1 mol / L.

[0059] The catalyst prepared by the above method is used in a method for catalyzing the synthesis of lactide, and can be used in a reaction using lactic acid as a raw material, especially in the depolymerization of lactic acid oligomers to prepare lactide.

[0060] Specifically, the method for catalytically synthesizing lactide using the above catalyst comprises the following steps:

[0061] (1) Polycondensation of lactic acid into oligomers: Lactic acid is subjected to esterification polycondensation reaction at a temperature of 100 to 185°C, a pressure of 2.5 to 10 KPaA, and a residence time of 4 to 15 hours. The water produced during the reaction is evaporated to obtain lactic acid oligomers;

[0062] (2) Depolymerization of lactic acid oligomers: The obtained lactic acid oligomers are mixed with the catalyst prepared above, and depolymerized at a temperature of 190-250° C., a pressure of 0.5-5 kPaA, a residence time of 0.5-3 h, and a catalyst concentration of 0.1%-5% to generate a lactide product, during which the lactide is continuously evaporated from the system.

[0063] The present invention is further explained below by more specific examples, but does not constitute any limitation.

[0064] In the depolymerization process mentioned in the following examples, the crude lactide yield is calculated as follows:

[0065] Crude lactide yield = crude lactide mass produced by the reaction / feed mass of lactic acid oligomers * 100%

[0066] The crude lactide product was diluted with acetonitrile and then measured for optical purity using gas chromatography. The gas chromatography analysis conditions were as follows: gas chromatography column: 0.25mm×0.25mm×30m capillary column with Rt-bDEXsm as the stationary phase; FID detector, vaporization chamber temperature 220°C, detector temperature 230°C, nitrogen carrier flow 1ml / min, hydrogen flow 40ml / min, air flow 400ml / min, injection volume 1μL. Analysis method: area normalization method.

[0067] The weight average molecular weight of lactic acid oligomers and depolymerization reactor residues was measured using GPC.

[0068] The molecular structure of the polymerization inhibitor loaded on the catalyst is detected by hydrogen spectrum, carbon spectrum and GPC. The repeating structural units that may appear in the polymerization inhibitor polymer are estimated based on the raw materials used for polymerization, the actual molecular weight is detected by GPC, and the molecular structure is determined by combining hydrogen spectrum and carbon spectrum.

[0069] The main raw materials used in the embodiments and comparative examples are as follows:

[0070] The raw material L-lactic acid comes from Jiangxi Musashiye Biochemical Co., Ltd., with a chemical purity of 90% and an optical purity of 99.97%;

[0071] Zinc acetate dihydrate comes from Beijing Yinuokai, purity>99%;

[0072] Stannous chloride dihydrate comes from Beijing Yinuokai, with a purity of >99%;

[0073] Anhydrous ethanol comes from Beijing Yinuokai, with a purity of 99.5%;

[0074] Polyethylene glycol was sourced from Shanghai Aladdin Biochemical Technology;

[0075] Ammonia water comes from Shanghai Aladdin Biochemical Technology, with a content of ≥25%;

[0076] Lactide was derived from Purac, with a purity of >99.5%;

[0077] Ethylene glycol monomethyl ether comes from Beijing Yinuokai, with a purity of ≥99%;

[0078] Sulfuric acid comes from Chinese medicine, with a purity of 98%;

[0079] Dichloromethane was sourced from Beijing Yinuokai, purity > 99%;

[0080] p-Hydroxyanisole comes from Beijing Yinuokai, with a purity of >99%;

[0081] Stannous octoate is sourced from Umicore, with a tin content of ≥28%.

[0082] Example 1 Preparation of catalyst loaded with polymerization inhibitor

[0083] Pour 21.9g zinc acetate dihydrate and 45g stannous chloride dihydrate into a beaker and add 150ml anhydrous ethanol to dissolve. Then add 6.7g polyethylene glycol with a molecular weight of 600 and 21g lactic acid and stir to dissolve. Drop 25% ammonia water into the beaker and adjust the pH value of the solution to 2. Stir with a glass rod during the adjustment process, then leave it to age for 12 hours to form a gel. The formed gel is separated by vacuum filtration and washed with ethanol. Place the gel in a drying oven and dry at 110°C for 3 hours. After drying, the dry gel is calcined at 500°C for 4 hours to obtain a composite ZnO-SnO substrate.

[0084] 35g of composite metal oxide substrate was mixed with 70g of polyethylene glycol with a molecular weight of 2000 and 70g of lactide in a flask. After heating to 130°C, the negative pressure was reduced to 15KPaA. 1g of lactic acid was added dropwise to the flask within 30min, and then the reaction was continued for 2h before stopping and restoring to normal pressure. 50g of lactide and 105g of ethylene glycol monomethyl ether were added to the flask, the temperature was raised to 140°C, the negative pressure was reduced to 5KpaA, and the reaction was continued for 2h before stopping. After the reaction solution was cooled, 1.5L of dichloromethane was added thereto, stirred and dissolved, and then 8L of anhydrous ethanol was added thereto to generate a white precipitate. The precipitate was filtered and separated and vacuum dried at 100°C for 6h. The dried precipitate was immersed in a 0.5mol / L sulfuric acid solution and soaked for 24 hours. Afterwards, it was filtered and separated, and the filter cake was vacuum dried at 100°C for 3 hours to obtain a catalyst loaded with an inhibitor.

[0085] After testing, the molecular weight of the inhibitor is about 3800. Figure 1 and Figure 2 The molecular structure is determined by the hydrogen spectrum and carbon spectrum:

[0086]

[0087] Example 2 Preparation of catalyst loaded with polymerization inhibitor

[0088] According to the process of Example 1, a metal oxide substrate was prepared.

[0089] 25g of composite metal oxide substrate was mixed with 75g of polyethylene glycol with a molecular weight of 4000 and 30g of lactide in a flask. After heating to 130°C, the negative pressure was reduced to 10KPaA. 3g of lactic acid was added dropwise to the flask within 45min, and then the reaction was continued for 1h before stopping and restoring to normal pressure. 30g of lactide and 125g of ethylene glycol monomethyl ether were added to the flask, the temperature was raised to 160°C, the negative pressure was reduced to 12KpaA, and the reaction was continued for 2h before stopping. After the reaction solution was cooled, 1.5Lml of dichloromethane was added thereto, stirred and dissolved, and 8L of anhydrous ethanol was added thereto to generate a white precipitate. The precipitate was filtered and separated and vacuum dried at 100°C for 6h. The dried precipitate was immersed in a 0.5mol / L sulfuric acid solution and soaked for 24 hours. Afterwards, it was filtered and separated, and the filter cake was vacuum dried at 100°C for 3 hours to obtain a catalyst loaded with an inhibitor.

[0090] After testing, the molecular weight of the inhibitor is about 4500. The molecular structure is determined by the comprehensive hydrogen spectrum and carbon spectrum:

[0091] Example 3 Preparation of catalyst loaded with polymerization inhibitor

[0092] Pour 21.9g zinc acetate dihydrate and 11.3g stannous chloride dihydrate into a beaker and add 30ml deionized water to dissolve. Then add 9.9g polyethylene glycol with a molecular weight of 200 and 16.6g lactic acid and stir to dissolve. Drop 25% ammonia water into the beaker, adjust the pH value of the solution to 1, stir with a glass rod during the adjustment process, and then leave it to age for 24 hours to form a gel. The formed gel is separated by vacuum filtration and washed with deionized water. Place the gel in a drying oven and dry at 110°C for 5 hours. After drying, the dry gel is calcined at 300°C for 5 hours to obtain a composite ZnO-SnO substrate.

[0093] 15g of composite metal oxide substrate was mixed with 45g of polyethylene glycol with a molecular weight of 2000 and 90g of lactide in a flask. After heating to 110°C, the negative pressure was reduced to 25KPaA. 1g of lactic acid was added dropwise to the flask within 30min, and then the reaction was continued for 2.5h before stopping and restoring to normal pressure. 50g of lactide and 50g of ethylene glycol monomethyl ether were added to the flask, the temperature was raised to 170°C, the negative pressure was reduced to 2.5KpaA, and the reaction was continued for 1h before stopping. After the reaction solution was cooled, 1.5L of dichloromethane was added thereto, stirred and dissolved, and 10L of anhydrous ethanol was added thereto until there was no white precipitate and then stopped. The precipitate was filtered and separated and vacuum dried at 100°C for 6h. The dried precipitate was immersed in a 1.5mol / L sulfuric acid solution and soaked for 24 hours. Afterwards, it was filtered and separated, and the filter cake was vacuum dried at 100°C for 3 hours to obtain a catalyst loaded with an inhibitor.

[0094] After testing, the molecular weight of the inhibitor is about 5800, and the molecular structure is determined by the comprehensive hydrogen spectrum and carbon spectrum:

[0095] Example 4 Preparation of catalyst loaded with polymerization inhibitor

[0096] Pour 52.5g zinc acetate dihydrate and 45g stannous chloride dihydrate into a beaker and dissolve in 150ml anhydrous ethanol. Then add 19g polyethylene glycol with a molecular weight of 200 and 68g lactic acid and stir to dissolve. Drop 25% ammonia water into the beaker, adjust the pH value of the solution to 1, stir with a glass rod during the adjustment process, and then leave it to age for 24 hours to form a gel. The formed gel is separated by vacuum filtration and washed with deionized water. Put the gel in a drying oven and dry it at 110°C for 5 hours. After drying, the dry gel is calcined at 400°C for 3 hours to obtain a composite ZnO-SnO substrate.

[0097] 100g of composite metal oxide substrate was mixed with 50g of polyethylene glycol with a molecular weight of 3000 and 150g of lactide in a flask. After heating to 150°C, the negative pressure was reduced to 45KPaA. 5g of lactic acid was added dropwise to the flask within 1h, and then the reaction was continued for 3h before stopping and restoring to normal pressure. 75g of lactide and 150g of ethylene glycol monomethyl ether were added to the flask, the temperature was raised to 180°C, the negative pressure was reduced to 1KpaA, and the reaction was continued for 0.5h before stopping. After the reaction solution was cooled, 3L of dichloromethane was added thereto, stirred and dissolved, and 15L of anhydrous ethanol was added thereto until there was no white precipitate and then stopped. The precipitate was filtered and separated and vacuum dried at 100°C for 6h. The dried precipitate was immersed in a 1.5mol / L sulfuric acid solution and soaked for 24 hours. Afterwards, it was filtered and separated, and the filter cake was vacuum dried at 100°C for 3 hours to obtain a catalyst loaded with an inhibitor.

[0098] After testing, the molecular weight of the inhibitor is about 5900, and the molecular structure is determined by the comprehensive hydrogen spectrum and carbon spectrum:

[0099] Example 5 Lactic acid prepolymerization to obtain lactic acid oligomers

[0100] The raw material of the prepolymerization reaction is a lactic acid aqueous solution containing 13% water. The reaction is a continuous reaction. Two glass reactors with a volume of 3L are used. The specific reaction process is as follows: the lactic acid aqueous solution is continuously fed into the No. 1 reactor at a feed rate of 400g / h. The temperature of the No. 1 reactor is 140°C, the pressure is 2.5KPaA, the residence time is 6h, and there is a distillation device on the top of the reactor to capture lactic acid in the water; the material of the No. 1 reactor continuously enters the No. 2 reactor. The temperature of the No. 2 reactor is 170°C, the pressure is 2.5KPaA, the residence time is 8h, and there is a distillation device on the top of the reactor to capture lactic acid in the water. The lactic acid oligomer obtained from the No. 2 reactor has a molecular weight of Mw=1520 as detected by GPC.

[0101] Example 6 Depolymerization of lactic acid oligomers to generate lactide

[0102] The depolymerization reaction was carried out in a glass reactor with a volume of 500 ml, which was a continuous reaction. 7.5 g of the catalyst prepared in Example 1 and 400 g of the lactic acid oligomer prepared in Example 5 were added to the reactor. The temperature in the reactor was gradually raised to 200°C, and the pressure was gradually reduced to 2KPaA to start the depolymerization reaction. At the same time, the lactic acid oligomer obtained in Example 5 was continuously fed at a rate of 400 g / h, and the crude lactide generated by depolymerization was collected at the top of the reactor through a distillation head. The crude lactide yield during the depolymerization process was calculated and the optical purity of the crude lactide was detected by gas chromatography. After 10 hours of continuous reaction, the residual sample of the reactor was taken to measure the weight average molecular weight.

[0103] Example 7 Depolymerization of lactic acid oligomers to generate lactide

[0104] 9.1 g of the catalyst prepared in Example 2 and 400 g of the lactic acid oligomer prepared in Example 5 were added to a reactor. The reaction was carried out according to the reaction conditions in Example 6. The crude lactide yield during the depolymerization process was calculated and the optical purity of the crude lactide was detected by gas chromatography. After the reaction was continued for 10 hours, the residual sample was taken from the reactor to measure the weight average molecular weight.

[0105] Example 8 Depolymerization of lactic acid oligomers to generate lactide

[0106] 3.3 g of the catalyst prepared in Example 3 and 400 g of the lactic acid oligomer prepared in Example 5 were added to the reactor. The temperature in the reactor was gradually raised to 210°C, and the pressure was gradually reduced to 1 KPaA to start the depolymerization reaction. At the same time, the lactic acid oligomer obtained in Example 5 was continuously fed at a rate of 800 g / h. The crude lactide generated by depolymerization was collected at the top of the reactor through a distillation head. The crude lactide yield during the depolymerization process was calculated and the optical purity of the crude lactide was detected by gas chromatography. After 10 hours of continuous reaction, the residual sample of the reactor was taken to measure the weight average molecular weight.

[0107] Example 9 Depolymerization of lactic acid oligomers to generate lactide

[0108] 18 g of the catalyst prepared in Example 4 and 400 g of the lactic acid oligomer prepared in Example 5 were added to the reactor. The temperature in the reactor was gradually raised to 220°C, and the pressure was gradually reduced to 0.5 KPaA to start the depolymerization reaction. At the same time, the lactic acid oligomer obtained in Example 5 was continuously fed at a rate of 1200 g / h, and the crude lactide generated by depolymerization was collected at the top of the reactor through a distillation head. The crude lactide yield during the depolymerization process was calculated and the optical purity of the crude lactide was detected by gas chromatography. After 10 hours of continuous reaction, the residual sample of the reactor was taken to measure the weight average molecular weight.

[0109] Comparative Example 1

[0110] 7.5 g of stannous octoate and 400 g of lactic acid oligomers prepared in Example 5 were added to the reactor. The reaction was carried out according to the reaction conditions in Example 6. The crude lactide yield during the depolymerization process was calculated and the optical purity of the crude lactide was detected by gas chromatography. After the reaction was continued for 10 hours, the residual sample was taken from the reactor to measure the weight average molecular weight.

[0111] Comparative Example 2

[0112] 3.3 g of stannous octoate and 400 g of lactic acid oligomers prepared in Example 5 were added to the reactor. The reaction was carried out according to the reaction conditions in Example 8. The crude lactide yield during the depolymerization process was calculated and the optical purity of the crude lactide was detected by gas chromatography. After the reaction was continued for 10 hours, the residual sample was taken from the reactor to measure the weight average molecular weight.

[0113] Comparative Example 3

[0114] 0.8 g of the metal oxide-based catalyst prepared in Example 1 and 400 g of the lactic acid oligomer prepared in Example 5 were added to a reactor, and 6.7 g of the polymerization inhibitor p-hydroxyanisole was added to the reactor. The reaction was carried out according to the reaction conditions in Example 6. The crude lactide yield during the depolymerization process was calculated and the optical purity of the crude lactide was detected by gas chromatography. After continuous reaction for 10 hours, the residual sample of the reactor was taken to measure the weight average molecular weight.

[0115] The reaction results of Examples 6 to 9 and Comparative Examples 1 to 3 are shown in Table 1.

[0116] Table 1

[0117] serial number Crude lactide yield / % Optical purity / % The average molecular weight of the kettle residue Mw Example 6 99.2 97.2 1730 Example 7 100 97.0 1547 Example 8 100 97.5 1530 Example 9 100 97.8 1645 Comparative Example 1 86.5 94.1 3904 Comparative Example 2 92.3 92.1 4590 Comparative Example 3 88.4 94.5 3245

[0118] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as limiting the present invention. Those skilled in the art will appreciate that, under the guidance of this specification, some modifications or adjustments may be made to the present invention. These modifications or adjustments should also be within the scope defined by the claims of the present invention.

Claims

1. A catalyst for catalytic synthesis of lactide, characterized in that: The catalyst is SO4 2- A catalyst having a polymerization inhibitor of formula I loaded on a modified ZnO-SnO composite metal oxide substrate, Among them, w=10~40, x=20~50, y=10~20, z=30~50.

2. A method for preparing the catalyst according to claim 1, characterized in that: The following steps are involved: 1) Precursors of zinc and tin are prepared into a solution with a solvent, and polyethylene glycol and lactic acid are added and mixed; 2) Add ammonia water to adjust the pH value to 1-3, and place it for 6-24 hours to form a gel; 3) separating the gel by filtration, repeatedly washing with a solvent until it becomes neutral, drying, and then calcining at a high temperature to obtain a ZnO-SnO composite metal oxide substrate; 4) mixing the ZnO-SnO composite metal oxide substrate obtained in step 3) with a certain amount of polyethylene glycol, lactide and lactic acid, and reacting them under a first reaction condition; adding a certain amount of lactide and ethylene glycol monomethyl ether to the product, and continuing the reaction under a second reaction condition; 5) After cooling, the product was dissolved in dichloromethane, anhydrous ethanol was added for precipitation, and the precipitate was dried in vacuum; 6) The vacuum-dried precipitate is immersed in a sulfuric acid solution, and then filtered and separated, and the filter cake is dried under vacuum conditions to obtain a catalyst.

3. The preparation method according to claim 2, characterized in that: In the step 1), the precursors of zinc and tin are selected from any one of nitrates, acetates or chlorides of zinc and tin, and the molar ratio of zinc to tin is 0.5-2.

4. The preparation method according to claim 3, characterized in that: In the step 1), the solvent is water or an alcohol solvent, and the concentration of the precursor after being prepared into a solution is 2-5 mol / L.

5. The preparation method according to claim 3, characterized in that: The molecular weight of the added polyethylene glycol is 200-600, the mass ratio of the polyethylene glycol to the precursor is 0.1-0.3, and the mass ratio of the added lactic acid to the precursor is 0.3-0.

7.

6. The preparation method according to claim 2, characterized in that: In the step 3), drying is performed at 100-150° C. for 3-5 hours.

7. The preparation method according to claim 6, characterized in that: The high temperature calcination temperature is 300-500°C and the calcination time is 3-5 hours.

8. The preparation method according to claim 2, characterized in that: The molecular weight of the polyethylene glycol added for the first time in step 4) is 2000-4000, the mass of the polyethylene glycol added is 50%-300% of the mass of the ZnO-SnO composite metal oxide substrate, the mass of the lactide added is 40%-300% of the mass of the polyethylene glycol, and the mass of the lactic acid added is 0.5%-10% of the mass of the polyethylene glycol.

9. The preparation method according to claim 8, characterized in that: In the step 4), the first reaction temperature is 100-150° C., the reaction pressure is 5-50 KPaA, and the reaction time is 0.5-3 h.

10. The preparation method according to claim 9, characterized in that: The reaction temperature is 110-140°C, the reaction pressure is 10-35KPaA, and the reaction time is 1-2.5h.

11. The preparation method according to claim 8, characterized in that: In the step 4), the lactide added for the second time is 40% to 150% of the mass of the polyethylene glycol added for the first time, and the mass of the ethylene glycol monomethyl ether added is 100% to 300% of the mass of the polyethylene glycol added for the first time.

12. The preparation method according to claim 11, characterized in that: In the step 4), the second reaction temperature is 120-180° C., the reaction pressure is 1-20 KPaA, and the reaction time is 0.5-3 h.

13. The preparation method according to claim 12, characterized in that: The reaction temperature is 130-170°C, the reaction pressure is 2.5-15KPaA, and the reaction time is 1-2.5h.

14. The preparation method according to claim 2, characterized in that: In the step 5), the amount of dichloromethane added is 5 to 20 times the mass of the product, and the volume of anhydrous ethanol added is 5 to 20 times the volume of dichloromethane.

15. The preparation method according to claim 14, characterized in that: The vacuum drying temperature is 100-150°C and the drying time is 3-10h.

16. The preparation method according to claim 2, characterized in that: The concentration of the sulfuric acid solution in step 6) is 0.5-2 mol / L, and the soaking time is 6-24 hours.

17. The preparation method according to claim 16, characterized in that: The drying temperature is 80-120°C and the drying time is 1-3 hours.

18. A method for catalytic synthesis of lactide, characterized in that: The catalyst of claim 1 or the catalyst prepared by the preparation method of any one of claims 2 to 17 is used in the reaction of preparing lactide by depolymerization of lactic acid oligomers.

19. The method according to claim 18, characterized in that The following steps are involved: 1) Polycondensation of lactic acid into oligomers: lactic acid oligomers are obtained by esterification polycondensation of lactic acid; 2) Depolymerization of lactic acid oligomers: The obtained lactic acid oligomers are mixed with the catalyst of claim 1 or the catalyst prepared by the preparation method of any one of claims 2 to 17, and depolymerization reaction is carried out under certain conditions to generate lactide products, and the lactide is continuously distilled off for collection.

20. The method for catalytically synthesizing lactide according to claim 18 or 19, characterized in that: The lactic acid is L-lactic acid or D-lactic acid.

21. The method for catalytically synthesizing lactide according to claim 20, characterized in that: In the step 1), the lactic acid is subjected to an esterification polycondensation reaction at a temperature of 100 to 185° C., a pressure of 2.5 to 10 KPaA, and a residence time of 4 to 15 hours, and the water produced during the reaction is evaporated to obtain lactic acid oligomers.

22. The method for catalytically synthesizing lactide according to claim 20, characterized in that: The reaction temperature of the depolymerization reaction in step 2) is 190-250° C., the reaction pressure is 0.5-5 KPaA, the residence time is 0.1-3 hours, and the catalyst mass concentration is 0.1%-5%.

Citation Information

Patent Citations

  • Preparation method of photoactive polylactic acid degradation material

    CN104004173A

  • Biodegradable plasticizer, medical anti-adhesion membrane, and preparation method of biodegradable plasticizer

    CN105396180A